Gastrointestinal Stromal Tumor in Patients Presenting to Khyber Teaching Hospital, Peshawar - Muhammad Ayaz, Muhammad Naeem Khattak, Yousaf Tahir, Munir Ahmad, Aamir Khan, Maira Riaz (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of presentations of gastrointestinal stromal tumor in patients presenting to Khyber Teaching Hospital, Peshawar. Study Design: Descriptive Cross Sectional Place and Duration of study: Department of General Surgery, MTI-KTH Peshawar. From 1st November, 2020 to 30 April, 2021. Methods: All patients were evaluated for their presentations (Abdominal Pain, Abdominal mass, Vomiting, Anemia, Weight loss and Hematemesis as per operational definition. All this data was noted and recorded on especially designed proforma. Results: As per frequencies and percentages for variable presentation, 42 (59.2%) patients had abdominal pain, 38 (53.5%) patients had abdominal mass, 36 (50.7%) patients had vomiting, 31 (43.7%) patients had anemia, 22 (31.0%) patients had weight loss while 11 (15.5%) patients had hematemesis. Conclusion: Our study demonstrated abdominal pain as the most common presentation of gastrointestinal stromal tumor in our local population as local evidence which was followed by abdominal mass and vomiting. Keywords: Abdominal Pain, Gastrointestinal Stromal Tumor, Vomiting